2005
DOI: 10.1074/jbc.m413737200
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-dependent Differences in U2AF Requirement for Splicing inAdenovirus-infected CellExtracts

Abstract: U2AF has been characterized as an essential splicing factor required for efficient recruitment of U2 small nuclear ribonucleoprotein to the 3-splice site in a pre-mRNA. The U2AF 65 subunit binds to the pyrimidine tract of the pre-mRNA, whereas the U2AF 35 subunit contacts the 3-splice site AG. Here we show that U2AF 35 appears to be completely dispensable for splicing in nuclear extracts prepared from adenovirus late-infected cells (Ad-NE). As a consequence, the viral IIIa and cellular IgM introns, which both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Also, our previous results have suggested that IIIa splicing is actively repressed in early infected cells by SR proteins binding to the 3RE (10), a repression that is relieved at the late phase of infection by a virus-induced dephosphorylation of SR proteins (23,24). Furthermore, the 3VDE, which binds U2AF inefficiently (11,12), adds to the low activity of IIIa splicing at early times of infection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, our previous results have suggested that IIIa splicing is actively repressed in early infected cells by SR proteins binding to the 3RE (10), a repression that is relieved at the late phase of infection by a virus-induced dephosphorylation of SR proteins (23,24). Furthermore, the 3VDE, which binds U2AF inefficiently (11,12), adds to the low activity of IIIa splicing at early times of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have shown that the 52,55K 3Ј splice site, which has an extended pyrimidine tract, requires U2AF 65 for activity (12). In contrast, the IIIa 3Ј splice site, which binds U2AF inefficiently (17), appears to be spliced by an U2AF-independent pathway (11,12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations